Analisis Morfologis Verba آمَنَ dalam Qs. Al-Baqarah Ayat 285: Kajian Wazn Berbasis Teori Ibn Faris - Lasmiati Radiah; Baiq Intan Amalia; Teddy Nur Hidayat; H. Akhmad Dasuki (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. Linguistic analysis of the Qur'an represents one of the most significant approaches to understanding divine messages in depth. Among the branches of Arabic linguistics that play a major role in interpreting Qur'anic meaning is morphology (ilmu sharaf), the study of word structure and the semantic changes produced by alterations in word form. Within the Qur'an, verbs occupy a central position as the primary elements conveying action and the core meaning of a verse. One verb that merits particular examination is āmana (آمَنَ) in QS. Al-Baqarah verse 285, as it is directly related to the concept of faith (iman) in Islam. This study aims to analyze the morphological form of the verb āmana using Ibn Faris's wazn theory as the primary analytical framework. Ibn Faris, through his work Maqayis al-Lughah, emphasizes the relationship between a root word and its fundamental meaning. The research employs a qualitative approach through library research, drawing on classical sharaf texts, Arabic dictionaries, Qur'anic commentary (tafsir), and relevant academic journals. The study focuses on identifying the morphological form of the verb, its wazn pattern, and its semantic implications for the meaning of the verse. The findings reveal that the verb āmana is a fi'il mazid following the pattern af'ala (أَفْعَلَ). The addition of a hamzah at the beginning of the word shifts the meaning from amina (أَمِنَ) to